On mikusinski's operators of fractional integration (1975)
In the field F of convolution quotients,  b∝ is the operator of integration of fractional order ∝ and b∝ f   Is the Riemann - Liouville integral of order   ∝ of f. In this paper we give a generalization of this operator, which is denoted as b∝,va . Some particular cases are mentioned and the inverse operator is obtained.